Pengaruh Sustainability Report dan Leverage terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi pada Perusahaan Perkebunan Kelapa Sawit yang Terdaftar di BEI 2022-2024 - Bagas Prasetyo; Dinar Riftiasari (Universitas Muhammadiyah Palembang, 2026)
In the era of globalization and increasing demands for business transparency, companies are required not only to achieve optimal financial performance but also to demonstrate responsibility for social and environmental aspects. Firm value reflects investors’ perceptions of a company’s performance and future prospects. In the palm oil plantation sector, sustainability issues become a major concern due to environmental risks and international regulatory pressures. This study aims to analyze the effect of sustainability reports and leverage on firm value and examine the moderating role of profitability. The study uses a quantitative approach with secondary data from palm oil plantation companies listed on the Indonesia Stock Exchange during 2022–2024, consisting of 13 companies and 38 observations. The results show that sustainability reports do not affect firm value, leverage has a positive and significant effect, and profitability does not moderate the relationship.